Climate smart cocoa value chains: Presentation at 6th European Cocoa Forum - Dubrovnik, Croatia - Lundy, Mark M.; Bunn, Christian; Castro, Fabio (2016)
What are the risks that the cocoa sector faces from climate change and what can be done to minimize those risks. Focus on telling a simple story for an industry audience.